2021
DOI: 10.1016/j.jag.2021.102458
|View full text |Cite
|
Sign up to set email alerts
|

Support vector regression for high-resolution beach surface moisture estimation from terrestrial LiDAR intensity data

Abstract: Highlights High-resolution beach surface moisture estimation from the LiDAR intensity data. No need to calibrate the intensity data in advance based on the Machine Learning. Detailed investigation of the impacts of SVR training samples’ size and density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 77 publications
1
2
0
Order By: Relevance
“…However, the linear kernel model performed less well than SVR rbf and SVR quad with R, RMSE and Bias values of about 0.69, 0.06m 3 /m 3 and −0.01m 3 /m 3 , respectively. It is important to mention that our finding were similar to those reported in previous studies [60], [61] which demonstrated that the SVR rbf provides the most superior simulation results, followed by polynomial kernel and linear kernel. In a similar vein, our statistical metrics are in the range of the performance exhibited by the investigation of [43] when using SVR with several features extracted from Sentinel-1&2 and Radarsat-2 remote sensing data.…”
Section: ) Support Vector Regression and Tree-based Algorithmssupporting
confidence: 91%
See 1 more Smart Citation
“…However, the linear kernel model performed less well than SVR rbf and SVR quad with R, RMSE and Bias values of about 0.69, 0.06m 3 /m 3 and −0.01m 3 /m 3 , respectively. It is important to mention that our finding were similar to those reported in previous studies [60], [61] which demonstrated that the SVR rbf provides the most superior simulation results, followed by polynomial kernel and linear kernel. In a similar vein, our statistical metrics are in the range of the performance exhibited by the investigation of [43] when using SVR with several features extracted from Sentinel-1&2 and Radarsat-2 remote sensing data.…”
Section: ) Support Vector Regression and Tree-based Algorithmssupporting
confidence: 91%
“…Likewise, [62] showed that the SVR algorithm driven by backscatter at VV polorisation extracted from the active microwave Advanced Scatterometer (ASCAT) estimates correctly soil moisture and their results, which are in agreement with our finding, exhibit minor variations depending on the different training/testing configurations. Kindly note that, in addition to its robustness in estimation soil moisture, and compared with SVR quad, SVR rbf exhibits lower computational complexity and less computational time [61]. Consequently, among the three proposed SVR algorithms, only RBF kernel will be adopted for testing the transferability processes.…”
Section: ) Support Vector Regression and Tree-based Algorithmsmentioning
confidence: 99%
“…SVR is suitable for nonlinearity and is resistant to outliers. This method has been applied to various hydrogeophysical problems such as hydraulic conductivity estimation from soil electrical spectra (Boadu, 2020) and soil moisture estimation from airborne and other datasets (Acharya et al, 2021;Achieng, 2019;Jin et al, 2021;Pasolli et al, 2011). SVR was performed using the R e1071 package (D. Meyer et al, 2021) function svm.…”
Section: Support Vector Regressionmentioning
confidence: 99%
“…Additionally, there are several machine learning algorithms such as, classification and regression trees (ART), Random Forest Regression (RFR) [11], support vector regression (SVR) [12], multiple linear regression modeling, boosted regression tree (BRT), artificial neural networks (ANN) [13] are used to predict soil moisture availability (Figure 1).…”
Section: Literature Reviewmentioning
confidence: 99%